Factors influence the online customer satisfaction towards food online delivery / Siti Sarah Solehen - Solehen, Siti Sarah (Faculty of Business and Management, 2018)
The main objective of this research is to study the factors that influence the customer satisfaction on online food delivery among customers in Malaysia. It is also to study either there are relationship exist between service quality, product quality, site ease and online customer satisfaction. These factors have been used to investigate whether all the factor have influence the customer satisfaction towards food online delivery. In order to views the effect on the customer satisfaction towards food online delivery, the data have been collected. All the data are obtained from the observation and the questionnaire that already been distributed to the customers among Malaysia who have an experience in using food online delivery service. The finding shows that all the factors give an impact tp the online customer satisfaction. According to the observation that have been made and the questionnaire that have been distributed, it was conclude that the customer are interested to use the food online delivery service if they satisfied with the food online service.